A review of the infection-associated cancers in North African countries. Issue 1 (December 2016) - Hussein, Wafaa; Anwar, Wagida; Attaleb, Mohammed; Mazini, Loubna; Försti, Asta; Trimbitas, Roxana-Delia; Khyatti, Meriem
Abstract Cancer is typically classified as a leading non-communicable disease; however, infectious agents, such asHelicobacter pylori (H. pylori ), hepatitis B virus (HBV), hepatitis C virus (HCV) and human papilloma virus (HPV), contribute significantly to the pathogenesis of various cancers. Less developed countries, including countries of the North African (NA) region, endure the highest burden of infection-related cancers. The five most common infection-associated cancers in NA in order of incidence are bladder cancer, cervical cancer, liver cancer, stomach cancer, and nasopharyngeal carcinoma. This review aims to outline the epidemiologic pattern of infection-associated cancers in five NA countries (namely: Morocco, Algeria, Tunisia, Libya and Egypt) highlighting the similarities and differences across the region. The present study employed an initial literature review of peer-reviewed articles selected from PubMed, ScienceDirect and World Health Organization (WHO) databases based on key word searches without restriction on publication dates. Original research articles and reports written in French, as well as data from institutional reports and regional meeting abstracts were also included in this extensive review. Egypt, Libya, Tunisia, Algeria and Morocco were selected to be the focus of this review.